Model Sistem Permintaan Bahan Pangan Rumah Tangga pada Masa Pandemi Covid-19 - Fani, Riyanda (Universitas Cokroaminoto Palopo, 2024)
Currently, the world is being shocked by the existence of Corona Virus Disease or better known as Covid-19, so that people who lack food ingredients also automatically increase because many people are affected by mass layoffs which results in mass unemployment. The absence of a fixed income for some residents has caused access to meet basic needs for food to increase. Of course, during this pandemic. In meeting the demand for foodstuffs, the QUAIDS model is used to be able to see the food demand system. The model is implemented in the ADDIE Model so that it can be analyzed, designed, developed, and implemented to the community in order to see the need for food during the Covid-19 pandemic.